Expanding Role of Type II Secretion in Bacterial Pathogenesis and Beyond - Cianciotto, Nicholas P; White, Richard C (Infection and immunity, 2017)
Type II secretion (T2S) is one means by which Gram-negative pathogens secrete proteins into the extracellular milieu and/or host organisms. Based upon recent genome sequencing, it is clear that T2S is largely restricted to the , occurring in many, but not all, genera in the , , , and classes. Prominent human and/or animal pathogens that express a T2S system(s) include , , , , , , , , , and T2S-expressing plant pathogens include , , , , , , and T2S also occurs in nonpathogenic bacteria, facilitating symbioses, among other things. The output of a T2S system can range from only one to dozens of secreted proteins, encompassing a diverse array of toxins, degradative enzymes, and other effectors, including novel proteins. Pathogenic processes mediated by T2S include the death of host cells, degradation of tissue, suppression of innate immunity, adherence to host surfaces, biofilm formation, invasion into and growth within host cells, nutrient assimilation, and alterations in host ion flux. The reach of T2S is perhaps best illustrated by those bacteria that clearly use it for both environmental survival and virulence; e.g., employs T2S for infection of amoebae, growth within lung cells, dampening of cytokines, and tissue destruction. This minireview provides an update on the types of bacteria that have T2S, the kinds of proteins that are secreted via T2S, and how T2S substrates promote infection.